Frequent callers to telephone helplines: new evidence and a new service model. Issue 1 (December 2016) - Pirkis, Jane; Middleton, Aves; Bassilios, Bridget; Harris, Meredith; Spittal, Matthew; Fedszyn, Izabela; Chondros, Patty; Gunn, Jane
Abstract Background This paper describes a program of work designed to inform a service model to address a challenge for telephone helplines, namely frequent callers. Methods We conducted a systematic literature review and four empirical studies that drew on different data sources—(a) routinely collected calls data from Lifeline, Australia's largest telephone helpline; (b) data from surveys/interviews with Lifeline frequent callers; (c) data from the Diagnosis, Management and Outcomes of Depression in Primary Care(diamond) study; and (d) data from Australia's National Survey of Mental Health and Wellbeing. Results Frequent callers represent 3 % of callers but make 60 % of calls. They are isolated and have few social supports but are not "time wasters"; they have major mental and physical health problems and are often in crisis. They make use of other services for their mental health problems. The circumstances under which they use telephone helplines vary, but current service models reinforce their calling behaviour. Conclusions The findings point to a service model that might better serve the needs of both frequent callers and other callers. The model involves offering frequent callers an integrated, tailored service in which they are allocated a dedicated and specially trained telephone crisis supporter (TCS), and given set calling times. It also involves promoting better linkages between telephone helplines and other services that provide mental health care, particularly general practitioners (GPs) and other primary care providers. The next step is to refine and test the model.